Early cataract surgery and affordable Sinskey hook goniotomy in Black and Afro-Latino glaucoma patients: a 6-month retrospective study - Laroche, Daniel; Adebayo, Ayobami; Brown, Aaron; Ng, Chester; Sakkari, Soheil (Frontiers in Ophthalmology, 2024)
The purpose of this study is to determine the realworld efficacy of phacoemulsification early cataract surgery and goniotomy with a Sinskey hook in patients with glaucoma.This study was conducted at Advanced Eye Care of NY, a private practice located in Manhattan, NY.This was a single-center, retrospective study of predominantly Black and Afro -Latino patients with glaucoma. These patients have undergone phacoemulsification early cataract surgery and goniotomy using an affordable and reusable straight Sinskey hook (Ambler 200um tip). Patients who underwent the above procedure with six months of follow up were included in this study. Investigated parameters were intraocular pressure, number of medications, mean deviation on visual field test, visual acuity, adverse events, and pre/post-operative spherical refractive error.Among all 38 eyes enrolled in the study undergoing surgery, goniotomy using a Sinskey hook with phacoemulsification, mean intraocular pressure was reduced from 16.45 mmHg at baseline to 13.24 mmHg at month six, a 19.5% reduction. The mean number of topical intraocular pressure lowering medications was reduced from 1.81 at baseline to 0.52 at month six. This is a 71% reduction in topical medications.Early cataract surgery and goniotomy performed with a Sinskey hook combined is an affordable microinvasive surgery and effective way to reduce intraocular pressure and the amount of ocular hypertensive medications used in Black and Afro -Latino patients with primary open angle glaucoma.